WhatsApp Bot Based Prayer Time Schedule Information System - Hamas, Nuril Fathoni (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2024)
Nowadays, it is very easy to find out the beginning of prayer times, because there are so many providers of prayer time schedule information, both on the internet and prayer time schedule applications. It would be more interesting if the prayer time schedule could be accessed via the WhatsApp application, which is an instant messaging application that is quite popular among the public today, so there is no need to install a special application or open a specific website to get the desired prayer time schedule. This paper aims to design a prayer time schedule information system based on WhatsApp Bot and test the verification of the current time schedule results obtained from the WhatsApp Bot. This study uses a research and development method with a descriptive approach. The results of this study are in the form of a prayer time schedule information system based on WhatsApp Bot which is built with NodeJS programming. Then from the accuracy test using the Bimas Islam website and several prayer time schedule providers, there is no difference in the results. Because the solar data used has a relatively similar level of accuracy, and the prayer time schedule calculation algorithm used is the same. So that the prayer time schedule produced by WhatsApp Bot has an accuracy that is worthy of being used as a reference for entering prayer times.